Pituitary deficiency and congenital infiltrating lipomatosis of the face in a girl with deletion of chromosome 1q24.3q31.1. Issue 2 (5th December 2013) - Capra, V.; Severino, M.; Rossi, A.; Nozza, P.; Doneda, C.; Perri, K.; Pavanello, M.; Fiorio, P.; Gimelli, G.; Tassano, E.; Di Battista, E.
ABSTRACT Interstitial deletions of the long arm of chromosome 1 are rare and they are classified as proximal or intermediate. The intermediate interstitial deletions span 1q24–1q32. We describe a 6‐year‐old girl with multiple pituitary hormone deficiency, severe cognitive impairment, bilateral cleft lip and palate, midline facial capillary malformation, erythema of hands and feet and dysplastic cranial vessels, low anti‐thrombin III activity, hemifacial overgrowth due to progressive infiltrating lipomatosis with bone overgrowth, marked vascular proliferation and erythema of hands and feet, and abnormal cranial vessels. The girl's karyotype showed an apparently de novo interstitial deletion 1q24.3q31.1, which was defined by array‐CGH. The deleted region contains numerous genes, but only eight (CENPL, LHX4, LAMC1, LAMC2, PTGS2, ANGPTL1, TNN, and TNR) are good candidates to explain, at least partially, the phenotype of the proposita. We, therefore, discuss the involvement of these genes and the observed phenotype. © 2013 Wiley Periodicals, Inc.